52nd AIAA/SAE/ASEE Joint Propulsion Conference 2016
DOI: 10.2514/6.2016-4826
|View full text |Cite
|
Sign up to set email alerts
|

Performance, Facility Pressure Effects, and Stability Characterization Tests of NASA’s 12.5-kW Hall Effect Rocket with Magnetic Shielding Thruster

Abstract: analysis of the discharge current waveforms showed that increasing the vacuum chamber background pressure resulted in a higher discharge current dominant breathing mode frequency. Finally, IVB maps of the TDU-1 thruster indicated that the discharge current became more oscillatory with higher discharge current peak-to-peak and RMS values with increased facility background pressure at lower thruster mass flow rates; thruster operation at higher flow rates resulted in less change to the thruster's IVB characteris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
30
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 16 publications
(21 reference statements)
0
30
0
Order By: Relevance
“…The FECT was partially described in a prior publication. 10 Following the recent deployments of medium power (1-10 kW) Hall thrusters on orbit, the community has developed renewed interest in the differences in the performance of Hall thrusters in ground facilities versus on-orbit. [13][14][15] To reduce the risk that the on-orbit behavior of the HERMeS cannot be predicted from ground test data, the team designed tests to characterize the finite background pressure effect, electrical configuration effect, and the effect of sputter-deposition on the operation of the HERMeS.…”
Section: Figure 1 a Diagram Of The Tdu Test Campaignmentioning
confidence: 99%
See 2 more Smart Citations
“…The FECT was partially described in a prior publication. 10 Following the recent deployments of medium power (1-10 kW) Hall thrusters on orbit, the community has developed renewed interest in the differences in the performance of Hall thrusters in ground facilities versus on-orbit. [13][14][15] To reduce the risk that the on-orbit behavior of the HERMeS cannot be predicted from ground test data, the team designed tests to characterize the finite background pressure effect, electrical configuration effect, and the effect of sputter-deposition on the operation of the HERMeS.…”
Section: Figure 1 a Diagram Of The Tdu Test Campaignmentioning
confidence: 99%
“…The thruster had also been power throttled over discharge powers ranging from 0.6 to 12.5 kW. 10 The cathode mass flow rate was maintained at 7% of the anode mass flow rate.…”
Section: A Thrusters and Test Matrixmentioning
confidence: 99%
See 1 more Smart Citation
“…The growth in interest and popularity of HETs has caused a corresponding increase in HET research, testing, and development programs both domestically and internationally [2][3][4]. Despite the similarities among the devices tested and measurements recorded at each of these facilities, the wide range of facility geometries, sizes, materials, and pumping capacities makes it difficult for researchers to compare datasets without the inclusion of facility-dependent corrections [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23]. It is therefore desirable to develop an understanding of how to quantify facility effects on HET operation and data collection so that facilitydependent testing artifacts can be corrected for and a facilityindependent understanding of the device performance can be achieved.…”
mentioning
confidence: 99%
“…Although several investigations into facility effects exist in the literature, most focus on the role of facility backpressure on plume properties and device operation. Previous studies have shown that increases in facility pressure result in artificial increases in device thrust and efficiency due to neutral ingestion or entrainment [5][6][7][8][9][10][11][12][13][14]16,17,[20][21][22]. Work has also been conducted linking background pressure to parasitic facility effects caused by resonant charge exchange (CEX) collisions.…”
mentioning
confidence: 99%